Interrelationships between affective disorders in the form of depression and obesity and overweight - A systematic review - Aleksandra Marczak; Julia Krawczuk vel Walczuk; Maria Maciąg; Maciej Sobczyk; Karolina Garbacz; Małgorzata Pasztelan; Jarosław Pulikowski; Aleksandra Muca; Małgorzata Słaboń; Joanna Baran (Quality in Sport)
Both depression and obesity are significant health, social and economic problems.